Effectiveness of ACIK (Anak Ceria dan Kreatif) Gymnastics Model Implementation to Improve Child's Kinesthetic Basic Motion (Department of Physical Education, Sport, Health and Recreation, 2020)
Kinesthetic intelligence is the movement to coordinate body movements using parts or the whole body to communicate and solve problem parts. This research uses a quantitative approach with a quasi-experimental method (quasi-experimental). The design used in this study is the one group control pretest-posttest design. This researcher used the TGMD 2 test instrument. Based on the results of the effectiveness test, it was proven that the average value of the experimental class's posttest effectiveness test results was 77.4048% greater than the results of the control class posttest score of 50.1343%. Then it can be concluded that the ACIK (Anak Ceria dan Kreatif) gymnastics model proved to be effectively applied to improve the kinesthetic basic motion of kindergarten students. From the results of these studies, it is necessary to submit a suggestion that is especially for kindergarten teachers should be more creative and innovative in designing and delivering learning materials, especially in physical motor material.